TROUBLESHOOTING AND REPAIR PERALATAN LISTRIK RUMAH TANGGA - Alimuddin Sa’ban Miru; Aminuddin Bakry; Zulhajji Zulhajji (Seminar Nasional Pengabdian Kepada Masyarakat, 2021)
Abstract : The main purpose of implementing community service activities is to provide basic knowledge and troubleshooting and repair skills to the community or youth who have dropped out of school in Rompegading Village, Liliriaja District, Soppeng Regency in terms of maintaining and repairing household electrical appliances. The rationale for this training activity is that the community or youth who have dropped out of school will no longer have difficulty solving problems in repairing household electrical appliances. This training is also carried out using the lecture, discussion, question and answer method, and simulation (training). It can be concluded that the results of community skills in troubleshooting and repairing household electrical appliances have increased significantly.Keywords: Troubleshooting, ARTL, Repair Skills